Ending intimate partner violence among women living with HIV: How attachment and HIV stigma inform understanding and intervention. (9th August 2021) - Davis, Katy; Dawson-Rose, Carol; Cuca, Yvette P.; Shumway, Martha; Machtinger, Edward
ABSTRACT: This mixed-methods, exploratory study examined why women living with HIV (WLHIV) stay in intimate partner violence (IPV) relationships and what helps end IPV in their lives. WLHIV (n = 108) who experienced IPV and were patients at two HIV primary care clinics in San Francisco completed quantitative surveys; 15 participants also completed a qualitative interview. Qualitative data showed HIV stigma was the most cited reason for staying in an IPV relationship, followed by substance use, and then by themes of attachment insecurity. Quantitative data indicated that most participants accessed HIV services and rated them as more helpful than other community resources to end IPV in their lives. Enduring attachment relationships with HIV medical and social service providers and their attachment-enhancing actions and attributes were critical to participants addressing IPV and coping with HIV stigma. This study highlights the important role that HIV providers and clinics can play in addressing IPV among WLHIV.